Taglish Code Switching as a Strategy in Teaching Mathematics - Asuncion, Quendell E.; Dagdag, Januard D. (Universitas Negeri Padang, 2025)
Language plays a vital role in understanding mathematical concepts, especially where English is not the learners’ first language. Despite the common use of Tag-lish in classrooms, research on its effectiveness in secondary mathematics under the new normal is limited. This study examined the effect of Tag-lish code switching on students’ mathematics achievement, attitude toward mathematics, and problem-solving efficacy using a pretest-posttest quasi-experimental design. The control group (n = 15) received pure English instruction, while the experimental group (n = 15) received Tag-lish instruction. Paired samples t-test and ANCOVA were used to analyze data. Both groups improved from pretest to posttest, but ANCOVA showed that the experimental group outperformed the control group in mathematics achievement and problem-solving efficacy. While both methods had similar effects on attitude toward mathematics, Tag-lish was more effective overall. The study recommends using Tag-lish code switching in teaching high school mathematics.